1983
DOI: 10.1161/01.cir.67.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between myocardial infarct size and occluded bed size in the dog: difference between left anterior descending and circumflex coronary artery occlusions.

Abstract: SUMMARY We compared myocardial infarct size produced by permanent occlusion of the middle left anterior descending (LAD) or circumflex (LCx) coronary artery in the anesthetized dog. The dogs were killed 3-10 days later, and the occluded coronary bed was visualized by postmortem arteriography. The outlines of the infarct and occluded bed were marked on tracings of weighed left ventricular (LV) rings and the size of the infarct and occluded bed was calculated by planimetry. For both arteries, infarct size and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…8,[15][16][17] This technique has been validated in our laboratory against staining methods such as monastral blue dye injection. 18 In brief, myocardial pieces with MBF Ͻ50% of the MBF in the equivalent remote-region piece during coronary occlusion constituted the risk region.…”
Section: Postmortem Delineation Of Microvascularobstruction Infarctementioning
confidence: 99%
“…8,[15][16][17] This technique has been validated in our laboratory against staining methods such as monastral blue dye injection. 18 In brief, myocardial pieces with MBF Ͻ50% of the MBF in the equivalent remote-region piece during coronary occlusion constituted the risk region.…”
Section: Postmortem Delineation Of Microvascularobstruction Infarctementioning
confidence: 99%
“…To minimize the influences of this variability and assess the effect of interven tions on myocardial infarct size accurately, several techniques have been developed for measuring the area at risk that could eventu ally evolve to necrosis [2][3][4][5], Even after cor rection for the area at risk, however, the per centage of the zone at risk that evolves to infarction varies among individual animals. Several other factors, including the amount of collateral blood flow [5][6][7][8][9], the duration of ischemia [6], the myocardial oxygen con sumption [8][9][10] and the coronary artery that is occluded [11], have been reported to influence the amount of necrosis within the risk zone under experimental conditions. Whether the extent of the zone at risk per se influences the percentage of the zone that develops infarction, however, remains a con troversial issue [5,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the extension of ischemia in the direction of the long-axis of the left ventricle varies greatly depending on the size and the stenotic coronary artery, the extensive ischemia extends to all levels toward long axis of left ventricle. 10) Therefore, the extension of ischemia toward long-axis of left ventricle indicates the severe ischemia or poor prognosis. 11) We found that the presence of exercise-induced chest pain was more closely related to the extension of ischemic burden toward the long-axis of the left ventricle than the total extent and depth of ischemic burden, although the extension of ischemic burden toward the long-axis of the left ventricle was closely related to the total extent and depth of ischemic burden.…”
Section: Discussionmentioning
confidence: 99%